Method for degrading waste cotton-polyester blended fabric through chemical-enzyme cascade reaction and application of method
Through the chemical-enzyme cascade reaction method, p-toluenesulfonic acid and PET hydrolase degrade cotton fibers and polyester fibers respectively, solving the problem of difficult fiber separation in textile waste recycling and achieving efficient and environmentally friendly fiber recycling.
Patent Information
- Application Number
- CN202411821879.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively recycle and separate cotton and polyester fibers in textile waste, resulting in waste of resources and environmental pollution.
The chemical-enzyme cascade reaction method is used to hydrothermal treatment using p-toluenesulfonic acid as an acid catalyst to degrade cotton fibers, and the crystallinity of polyester fibers is reduced by melting treatment. Finally, the enzymatic reaction is performed using PET hydrolase to achieve efficient separation and recovery of fibers.
It realizes efficient separation and recycling of cotton fibers and polyester fibers, and has the advantages of low equipment requirements, high safety, mild reaction conditions, high reaction efficiency and easy separation of products. It provides an efficient and environmentally friendly textile waste recycling method.
Smart Images

Figure CN119799808A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile waste recycling, and specifically relates to a method for degrading waste polyester-cotton blended fabrics by chemical-enzyme cascade reaction and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] As productivity and living standards improve, the demand for textiles, especially clothing, has steadily increased, while the length of use has gradually shortened. In 2000, global fiber production reached 58 million tons, and by 2019, production had almost doubled to 111 million tons, while generating a large amount of waste. However, the recycling technology of textile waste has not kept pace, and only a small part is recycled and reused. At present, most textile waste is either landfilled or incinerated, resulting in serious environmental pollution and waste of resources. The development of petrochemical technology has enabled the production of synthetic fibers to exceed that of natural fibers. Polyester fiber, mainly made of polyethylene terephthalate (PET), currently accounts for about 52% of total fiber production. The second most abundant fiber is cotton, which belongs to the natural fiber category, accounting for 24%, and is mainly composed of cellulose. Many textiles are interwoven with multiple fibers, especially polyester-cotton blended fabrics. However, this blend of fibers poses a major challenge to recycling.
[0004] In recent years, the use of PET hydrolase to degrade PET as an energy-saving and environmentally friendly PET recycling method has received widespread attention. Currently, PET hydrolase is mainly used for the recycling of PET bottles and has not yet been applied to the field of polyester fiber recycling. PET hydrolase can effectively degrade PET with a crystallinity of less than 20%, but the crystallinity of polyester fibers is usually 30-40%, so thermomechanical treatment is required to reduce the crystallinity. This process will carbonize the cotton fibers in the blend, resulting in resource waste and polyester pollution. Therefore, cotton fibers and polyester fibers must be separated during the recycling process. There are currently four main separation strategies: solvent dissolution, enzyme degradation, acidic hydrolysis, and acid-catalyzed hydrothermal treatment. Among them, acid-catalyzed hydrothermal treatment balances cost, efficiency, and environmental sustainability, making it a promising recycling strategy in industrial applications. Currently commonly used acid catalysts such as citric acid and hydrochloric acid are difficult to recycle, and there are certain environmental pollution and increased environmental protection costs. Summary of the invention
[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a method for degrading waste polyester-cotton blended fabrics by chemical-enzyme cascade reaction and its application. Specifically, the present invention creatively proposes a method for chemical-enzyme hydrolysis cascade reaction of using p-toluenesulfonic acid (TsOH) as an acid catalyst to catalyze the degradation of cotton fibers in mixed textiles, melt-treating the remaining polyester fibers to reduce the crystallinity, and finally using PET hydrolase to degrade the polyester fibers. The method has the advantages of high efficiency, safety, green environmental protection, etc. Based on the above research results, the present invention is completed.
[0006] Specifically, the technical solution of the present invention is as follows:
[0007] The first aspect of the present invention provides a method for degrading waste polyester-cotton blended fabrics by chemical-enzyme cascade reaction, comprising the following steps:
[0008] S1, subjecting the mixed textile to an acid-catalyzed hydrothermal treatment in an aqueous solution of p-toluenesulfonic acid to obtain a mixed solution;
[0009] S2, filtering the mixed solution obtained in step S1 through a sieve to obtain polyester fibers; filtering the remaining mixed solution through a filter membrane, washing, and drying to obtain microcrystalline cellulose;
[0010] S3, subjecting the polyester fiber obtained in step S2 to melt treatment, cooling to obtain amorphous polyester, and further crushing to obtain polyester powder;
[0011] S4, mixing the polyester powder obtained in step S3 with PET hydrolase and performing enzymatic hydrolysis reaction to obtain terephthalic acid (TPA) and ethylene glycol (EG).
[0012] The second aspect of the present invention provides application of the above method in recycling textile waste.
[0013] Beneficial technical effects of one or more of the above technical solutions:
[0014] The above technical solution combines chemical method and biological method, uses recyclable solid organic acid TsOH and biological PET hydrolase as catalysts for hydrolysis of cotton fiber and polyester fiber respectively, and has the advantages of low equipment requirements, high safety, mild reaction conditions, high reaction efficiency, easy product separation, green and environmental protection, etc., and provides an efficient and environmentally friendly method for industrial recycling of polyester-cotton blended waste, which has important practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0016] Figure 1The present invention is a flow chart of the chemical-enzymatic hydrolysis cascade reaction for degradation and recovery of mixed textiles.
[0017] Figure 2 The MCC is produced by hydrolyzing the pure cotton material of the present invention by TsOH.
[0018] Figure 3 It is the mass and yield of the solid (MCC) remaining after the pure cotton material of the present invention is hydrolyzed by TsOH catalysis.
[0019] Figure 4 It is the concentration and conversion rate of Glc produced after the pure cotton material of the present invention is hydrolyzed by TsOH.
[0020] Figure 5 It is the concentration and conversion rate of HMF produced after the pure cotton material of the present invention is hydrolyzed by TsOH.
[0021] Figure 6 It is the concentration and conversion rate of furfural produced after the pure cotton material of the present invention is catalyzed and hydrolyzed by TsOH.
[0022] Figure 7 The PET hydrolase of the present invention degrades the pretreated polyester fiber to produce MHET and TPA.
[0023] Figure 8 The MCC is produced after the mixed textile of the present invention is hydrolyzed by TsOH.
[0024] Fig. 9 The electron microscope observation is for the MCC produced after the mixed textile of the present invention is hydrolyzed by TsOH.
[0025] Fig.10 It is the mass and yield of the residual solid (MCC) after the mixed textile of the present invention is hydrolyzed by TsOH catalysis.
[0026] Fig.11 It is the concentration and conversion rate of the by-products produced after the mixed textile of the present invention is catalyzed and hydrolyzed by TsOH.
[0027] Fig.12 It is the yield of the polyester fibers remaining after the mixed textile of the present invention is catalytically hydrolyzed by TsOH.
[0028] Fig.13 It is the degradation rate of polyester fiber degraded by PET hydrolase LCC-A2 in the bioreactor at 70-78°C.
[0029] Fig.14 It is the degradation rate of polyester fiber degraded by PET hydrolase LCC-A2 in the bioreactor at 70-78°C.
[0030] Fig.15The product composition of the polyester fiber is degraded by the PET hydrolase LCC-A2 in a bioreactor at 78°C.
[0031] Fig.16 The product composition is obtained by degrading polyester fiber by PET hydrolase LCC-A2 in a bioreactor at 70°C. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0034] In view of the current recycling difficulties caused by mixing different fiber materials, as well as the harsh chemical recycling reaction conditions and the easy environmental pollution, a typical embodiment of the present invention provides a method for degrading waste polyester-cotton blended fabrics by chemical-enzyme cascade reaction, comprising the following steps:
[0035] S1, subjecting the mixed textile to an acid-catalyzed hydrothermal treatment in an aqueous solution of p-toluenesulfonic acid to obtain a mixed solution;
[0036] S2, filtering the mixed solution obtained in step S1 through a sieve to obtain polyester fibers; filtering the remaining mixed solution through a filter membrane, washing, and drying to obtain microcrystalline cellulose;
[0037] S3, subjecting the polyester fiber obtained in step S2 to melt treatment, cooling to obtain amorphous polyester, and further crushing to obtain polyester powder;
[0038] S4, mixing the polyester powder obtained in step S3 with PET hydrolase and performing enzymatic hydrolysis reaction to obtain terephthalic acid and ethylene glycol.
[0039] Among them, in the step S1, the mixed textile is made of polyester fiber (polyester) and cotton fiber, which can be production waste in the form of yarn and cloth, as well as industrial and agricultural production and daily necessities such as clothing, home textiles, bags, ropes, etc., without specific limitation here. The cotton fiber ratio is 0-100%, and the polyester fiber ratio is 0-100%; further, the cotton fiber and polyester fiber are neither 0 nor 100% at the same time.
[0040] The concentration of p-toluenesulfonic acid in the aqueous solution of p-toluenesulfonic acid may be 0.05-1%, further 0.1-1%, such as 0.1%, 0.5% and 1%.
[0041] Toluenesulfonic acid is a commonly used, cheap, solid organic strong acid with the potential to hydrolyze cellulose to produce microcrystalline cellulose (MCC) and glucose (Glc). MCC plays an important role in the fields of pharmaceuticals, food, cosmetics, and high-tech materials. A significant advantage of TsOH is that it is recyclable. The solubility of TsOH decreases at low temperatures, so it can be recovered by low-temperature crystallization after concentration. In addition, cross-linked resins can also be used for recovery, which is a more environmentally friendly option compared to traditional strong acids. Therefore, the present invention selects toluenesulfonic acid for catalytic hydrothermal treatment. Of course, the catalyst of step S1 can also be selected from green solid acids such as aluminosilicates (such as ZSM-5), solid phosphoric acid (such as aluminum phosphate), and metal organic frameworks (MOFs) with acidic sites.
[0042] The mass volume ratio of the mixed textile to the aqueous solution of p-toluenesulfonic acid is 1:10-30 (g / mL), further 1:20.
[0043] The reaction temperature is 130-150° C., and the reaction time is 6-12 h. To make the reaction more complete, stirring is performed during the reaction, and the stirring speed is 30-60 rpm, preferably 40 rpm.
[0044] In the step S2, the mesh size of the sieve is 30-50 meshes; in a specific embodiment of the present invention, the sieve can be a polytetrafluoroethylene sieve.
[0045] The filtration pore size of the filter membrane is no greater than 0.6 μm, and further is 0.45 μm. In a specific embodiment of the present invention, the filter membrane may be a polytetrafluoroethylene filter membrane.
[0046] The drying temperature may be 40-50° C., and the drying time may be 6-10 hours.
[0047] In the step S3, the melt treatment temperature is 240-290° C., and the treatment time is 1-30 min. The melt treatment can be performed in an extruder or an oven, which is not specifically limited here.
[0048] The pulverization can be performed by grinding, specifically by grinding in a grinder under liquid nitrogen freezing conditions, and the specific processing conditions are: power of 60-80%, time of 0.5-5min, preferably 75%, time of 1min.
[0049] In the step S4, the enzymatic hydrolysis reaction is carried out in a liquid phase environment, and the specific reaction conditions are: the reaction temperature is not higher than 85°C, further including 70-78°C, the reaction time is 1-20h, and the rotation speed is 100-500rpm. In order to ensure good enzymatic activity of PET hydrolase, so that the enzymatic hydrolysis reaction proceeds smoothly, the liquid phase environment can be provided by a buffer, specifically a phosphate buffer with a pH value of 8.5.
[0050] In another specific embodiment of the present invention, the concentration of the polyester powder in the enzymatic reaction system is 1-300 g / L, preferably 10 g / L, and the added amount of the PET hydrolase is 0.01-1% by mass of the polyester powder, preferably 0.3%.
[0051] The PET hydrolase can specifically be any known high-activity polyester degrading enzyme, such as LCC, IsPETase, TfCut, PHL7, HiC, BhrPETase and variants thereof; preferably LCC-A2:H183Y / N213D, which has been disclosed in CN116286727A and is a cutinase mutant obtained by the inventor's team in the early stage, which has good affinity for PET and high PET hydrolysis activity.
[0052] In another specific embodiment of the present invention, the pH of the enzymatic hydrolysis reaction system is maintained at a weak alkaline pH, further at pH 8.5, which can be maintained by adding alkali (such as NaOH).
[0053] In another specific embodiment of the present invention, there is provided application of the above method in recycling textile waste.
[0054] The present invention is further explained by the following examples, but they are not intended to limit the present invention. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0055] Example
[0056] 1. Hydrothermal treatment of cotton fibers catalyzed by TsOH
[0057] Experimental method: A hydrothermal reactor and a homogeneous reactor with a polytetrafluoroethylene sleeve were used to react, and 0.25 g of cotton fiber was treated with 5 mL of TsOH solution of different concentrations (0.05%, 0.1%, 0.5% and 1%). The concentration of Glc was detected by biosensor, and the concentration of other byproducts such as 5-hydroxymethylfurfural (HMF) and furfural was detected by high performance liquid chromatography. MCC was obtained by filtration using a 0.45 μm polytetrafluoroethylene filter, dried in an oven at 50 ° C for 6 h, and weighed.
[0058] Experimental process: First, the reaction was carried out at 110°C. When 1% TsOH solution was reacted for 12h, they lost their original form and turned into powder. The filtered solid contained powder and residual fiber, indicating incomplete hydrolysis. Extending the reaction time to 24h and 36h, the degree of hydrolysis was further improved and the fiber content decreased. The remaining solids accounted for 80-90% of the original mass, and about 7% of the cellulose was hydrolyzed to Glc. In addition, although the appearance remained intact, Glc was detected in the reaction system containing 0.5% TsOH, indicating that the cotton fiber was partially hydrolyzed. 0.05% and 0.1% TsOH at this temperature could not catalyze the hydrolysis of cotton fibers.
[0059] At 130°C, 0.5% and 1% TsOH can convert cotton fibers into MCC, and no obvious fiber residues are left after 0.5% reaction for more than 9 hours and 1% reaction for more than 6 hours. However, further extending the reaction time will cause the MCC color to darken, indicating that Glc is being oxidized to produce by-products such as 5-hydroxymethylfurfural (HMF) and furfural. The proportion of residual solid mass remains between 80-90%, and the Glc conversion rate accounts for 7-10% of cellulose. MCC and Glc are still the main hydrolysis products. At this temperature, 0.05% and 0.1% TsOH still cannot catalyze the hydrolysis of cotton fibers.
[0060] At 150°C, 0.1% TsOH also catalyzes the degradation of cotton fiber to MCC, but complete conversion requires 36 hours, at which point the MCC color turns dark brown and contains byproduct impurities. When the TsOH concentration is 0.5%, only 6 hours are required. When the TsOH concentration is 1%, only 3 hours are required. Strong reaction conditions lead to complex product compositions that are difficult to control, increase costs, and are economically inefficient.
[0061] Based on the three principles of full hydrolysis of cotton fiber, MCC as the main product, and mild reaction conditions, five conditions were selected for further analysis and comparison: 0.5% TsOH-130℃-9h, 0.5% TsOH-130℃-12h, 0.5% TsOH-150℃-6h, 0.5% TsOH-150℃-9h and 0.5% TsOH-150℃-12h. The substrates were ordinary cotton fiber (O-cotton) and combed cotton fiber (C-cotton). Combed cotton removes shorter fibers, is smoother, and is less prone to pilling. Under these conditions, both fibers can be completely hydrolyzed into powder ( Figure 2 ), except for 0.5% TsOH-150℃-12h, the MCC yield is higher than 80% ( Figure 3 ). Glc is the main byproduct. After reacting at 150℃ for 12h, the Glc concentrations of O-Cotton and C-Cotton were 4.37g / L and 5.07g / L, respectively, and the conversion rate was 7.5-9.0% ( Figure 4). HMF concentration is 0.109g / L and 0.111g / L ( Figure 5 ), while the furfural concentrations were 0.043 g / L and 0.031 g / L ( Figure 6 ).
[0062] 2. PET hydrolase catalyzes the degradation of polyester fibers
[0063] Experimental method: PET hydrolase LCC-A2 was obtained after expression and purification by Escherichia coli. Polyester fiber was melted in a high-temperature oven at 280°C and quickly cooled in cold water. Then, the sample was immersed in liquid nitrogen for 3 minutes and ground into powder using a grinder with the grinder parameters of 75% power and 1 minute. 30 μg of purified enzyme and 10 mg of polyester fiber powder were added to 1 mL of 0.1 M phosphate buffer (pH 8.5) and incubated at 72°C for 2 hours. 1 mL of acetonitrile was added to terminate the reaction, and the concentrations of the product terephthalic acid (TPA) and the intermediate product MHET were detected using high performance liquid chromatography.
[0064] Experimental process: The high crystallinity of untreated polyester fibers inhibited the function of PET hydrolase. After 2 hours of catalysis, no hydrolysis products were detected ( Figure 7 ). The polyester fiber powder with reduced crystallinity after pretreatment can be efficiently degraded. 12.6mM MHET and 7.8mM TPA were detected after 2h reaction at 72℃, which is equivalent to 39% degradation of polyester fiber.
[0065] 3. Chemical-enzymatic hydrolysis cascade method for degradation and recovery of polyester-cotton blended textiles
[0066] Experimental method: A hydrothermal reactor with a polytetrafluoroethylene sleeve and a homogeneous reactor were used for the reaction, and 0.25 g of polyester-cotton blended textiles were treated with 5 mL of 0.5% TsOH solution. The concentration of Glc was detected using a biosensor, and the concentration of other byproducts such as 5-hydroxymethylfurfural (HMF) and furfural was detected using high-performance liquid chromatography. Polyester fibers were obtained by filtering with a 30-mesh polytetrafluoroethylene mesh, and the remaining reaction solution was filtered with a 0.45 μm polytetrafluoroethylene filter membrane to obtain MCC, which was dried in an oven at 50°C for 6 hours and weighed. The obtained polyester fibers were melt-crushed.
[0067] A 100 mL bioreactor containing 50 mL of reaction buffer (0.1 M phosphate buffer, pH 8.5), 0.5 g of polyester fiber powder and 1.5 mg of PET hydrolase was reacted at 70-78 ° C and 300 rpm for 8 hours. The pH value of the reaction system was maintained at 8.5 with 0.25 M NaOH through a pH control system. The consumption of NaOH was used to calculate the production of TPA and the degradation rate of polyester fiber based on the stoichiometric relationship of producing 1 M TPA per 2 M NaOH consumed. The degradation product components were analyzed by high performance liquid chromatography.
[0068] Experimental procedure: A chemical-enzymatic hydrolysis cascade method was developed by combining the chemical hydrolysis of cotton fibers using TsOH with the enzymatic hydrolysis of polyester fibers using PET hydrolase. In order to test the effectiveness of this method, mixed textiles with different polyester (PET) and cotton ratios on the market were selected as substrates for reaction. The PET / cotton ratios of the materials were: 80% PET / 20% cotton (T80 / C20), 65% PET / 35% cotton (T65 / C35) and 40% PET / 60% cotton (T40 / C60), where the cotton of T40 / C60 was combed cotton. The polyester fibers wrapped around the cotton fibers inhibited degradation, so higher temperature reaction conditions were used, 0.5% TsOH-150℃-6h, 0.5% TsOH-150℃-9h and 0.5% TsOH-150℃-12h.
[0069] After 6 hours of hydrothermal treatment, the remaining fiber weight was very close to the theoretical polyester fiber content, indicating that most of the cotton fibers had been hydrolyzed, leaving stable polyester fibers that would not be degraded by TsOH. The MCC obtained after filtration was uniform and fine, and the color darkened with increasing reaction time. The MCC yields of T80 / C20 and T65 / C35 at 6 hours were 65.8% and 64.7%, respectively, with T40 / C60 having a higher yield of 77%. In order to minimize the formation of by-products, the conditions of 0.5% TsOH-150℃-6h were selected for formal experiments.
[0070] Repeated experiments confirmed the high stability of the TsOH-catalyzed hydrothermal treatment process. MCC was in a uniform powder form ( Figure 8 , Fig. 9 ), the yields were 80.7%, 70.9% and 86.1% respectively ( Fig.10 The main byproduct is still Glc. 10.6% of cotton fiber is converted to Glc in T80 / C20, while the conversion rates of T65 / C35 and T40 / C60 are 6% and 6.2%, respectively. The conversion rates of other byproducts HMF and furfural are less than 1% ( Fig.11The remaining fiber mass after treatment was 96%, 103% and 104% of the theoretical polyester content, respectively. This indicates that the cotton fiber was almost completely hydrolyzed, achieving effective separation of cotton fiber and polyester fiber in the blended fabric ( Fig.12 ).
[0071] PET hydrolase LCC-A2 was used to degrade polyester fibers in a bioreactor. When reacting at 78°C, the degradation rate was faster in the early stage, and 34% of the polyester fibers were degraded within 1 hour. However, after 2 hours, the degradation rate slowed down due to the increase in crystallinity of the polyester fibers at high temperatures. After 8 hours, only 63.8% of the polyester fibers were degraded ( Fig.13 ), the maximum degradation rate is 149.6g TPAeq. L -1 h - 1 g enzyme -1 ( Fig.14 The degradation of polyester fiber is very thorough, with the intermediate degradation product MHET accounting for only 0.49% and the complete degradation product TPA accounting for 99.51% ( Fig.15 ).
[0072] The reaction temperature was lowered to slow down the recrystallization process of the polyester fiber. At 70°C, the degradation rate of the polyester fiber increased steadily, and 66.8% was degraded within 8 hours, which was higher than the degradation rate at 78°C ( Fig.13 ). The maximum degradation rate is 87.3g TPAeq. L - 1 h -1 g enzyme -1 ( Fig.14 The ratio of final degradation products is similar to that at 70°C, with almost no intermediate products ( Fig.16 ).
[0073] Matters not covered by the present invention are known technologies.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for degrading waste polyester-cotton blended fabrics by chemical-enzyme cascade reaction, characterized in that: The steps include: S1, subjecting the mixed textile to an acid-catalyzed hydrothermal treatment in an aqueous solution of p-toluenesulfonic acid to obtain a mixed solution; S2, filtering the mixed solution obtained in step S1 through a sieve to obtain polyester fibers; filtering the remaining mixed solution through a filter membrane, washing, and drying to obtain microcrystalline cellulose; S3, subjecting the polyester fiber obtained in step S2 to melt treatment, cooling to obtain amorphous polyester, and further crushing to obtain polyester powder; S4, mixing the polyester powder obtained in step S3 with PET hydrolase and performing enzymatic hydrolysis reaction to obtain terephthalic acid and ethylene glycol.
2. The method according to claim 1, characterized in that In the step S1, the mixed textile is made of polyester fiber and cotton fiber; The concentration of p-toluenesulfonic acid in the aqueous solution of p-toluenesulfonic acid is 0.05-1%, further 0.1-1%; The mass volume ratio of the mixed textile to the aqueous solution of p-toluenesulfonic acid is 1:10-30 (g / mL).
3. The method according to claim 1, characterized in that In step S1, the reaction temperature is 130-150° C., and the reaction time is 6-12 h. Stirring is performed during the reaction, and the stirring speed is 30-60 rpm. The catalyst selected for acid catalysis in step S1 is also selected from green solid acids, which include aluminosilicates (further including ZSM-5), solid phosphoric acid (further including aluminum phosphate) and metal organic frameworks (MOFs) combined with acidic sites.
4. The method according to claim 1, characterized in that In step S2, the mesh size of the sieve is 30-50 meshes; The filtration pore size of the filter membrane is no greater than 0.6 μm, and further is 0.45 μm.
5. The method according to claim 1, characterized in that In step S2, the drying temperature is 40-50° C. and the drying time is 6-10 hours.
6. The method according to claim 1, characterized in that In the step S3, the melting treatment temperature is 240-290° C., and the treatment time is 1-30 min.
7. The method according to claim 1, characterized in that In the step S3, the pulverization is performed by grinding.
8. The method according to claim 1, characterized in that In step S4, the enzymatic hydrolysis reaction is carried out in a liquid phase environment, and the specific reaction conditions are: the reaction temperature is not higher than 85°C, further 70-78°C, the reaction time is 1-20h, the rotation speed is 100-500rpm, and the liquid phase environment is provided by a buffer solution, specifically a phosphate buffer solution with a pH value of 8.
5.
9. The method according to claim 1, characterized in that In the step S4, the concentration of the polyester powder in the enzymatic reaction system is 1-300 g / L, and the amount of the PET hydrolase added is 0.01-1% of the mass of the polyester powder; The PET hydrolase is LCC, IsPETase, TfCut, PHL7, HiC, BhrPETase and variants thereof; preferably LCC-A2: H183Y / N213D; Furthermore, the pH of the enzymatic reaction system is maintained at a weak alkaline level, further at pH 8.
5.
10. Use of the method according to any one of claims 1 to 9 in the recycling of textile waste.
Citation Information
Patent Citations
Cutinase variant as well as preparation method and application thereof in plastic degradation
CN116286727A
Cited By
Old clothes and textile recycling method and control system and device
CN121222780A